Glucose utilization by the trained heart: the molecular mechanisms behind fuel choice - Nogueira-Ferreira, Rita; Moreira-Gonçalves, Daniel; Santos, Mário; Leite-Moreira, Adelino; Lira, Fabio Santos [UNESP]; Ferreira, Rita (Elsevier, 2023)
The heart is capable of using all types of substrates to meet the energetic demands made by the contraction function, and it adjusts its substrate utilization in response to environmental alterations. Glucose is the preferred fuel during stress conditions such as ischemia and adrenergic stimulation. In addition to glycolysis as an energy-producing pathway, other pathways related to glucose metabolism, such as the hexosamine biosynthetic pathway and pentose phosphate pathway, also support the metabolic and functional needs of the heart.The cardiac beneficial effects of exercise training are undisputedly recognized. Exercise training has been recommended for cardiovascular disease prevention and treatment. However, the understanding of the metabolic pathways associated with these effects remains a topic of research. This has been a challenge since the physiological response to exercise training is dependent on the intensity, duration, frequency, and type of exercise as well as the environmental conditions. However, the knowledge of the metabolic adaptations of the heart to exercise training not only can contribute to a better comprehension of the molecular mechanisms associated with exercise training effects but can also provide clues to novel therapeutic targets.This chapter overviews glucose metabolism in the heart and highlights the role of glycolysis and its regulation of the cardiac remodeling induced by exercise training.
Keywords: Exercise training; glycolysis; heart; lactate; metabolic signaling